Social support as a key factor in the health promotion model: influencing diabetic wound prevention behavior - Suyanto, Suyanto; Sukartini, Tintin; Noor, Mohammad Arifin (Intelektual Pustaka Media Utama, 2025)
Diabetic foot wounds are a serious problem that threatens the quality of life of diabetes patients. Individual factors, family, and social support have an important role in preventing diabetic foot wounds. This research aims to determine the aspects of social support in preventing diabetic foot wounds. The research employed a cross-sectional design, involving 120 respondents. The Modified Diabetic Foot Care Behavior (MD FCB) instrument was used to assess behavior related to diabetic foot care. Data analysis was conducted using logistic regression. The results indicated a positive correlation between high levels of social support and the prevention of diabetic foot wounds. In assessing patient knowledge about foot care, it was found that 20 people (16.7%) had poor knowledge. Additionally, low family support was seen in 23 people (19.2%), low peer support in 17 people (14.2%), and low support from health workers in 15 people (12.5%). Furthermore, 42 people (35%) exhibited poor behavior in preventing foot wounds. The Chi-square test revealed a significant influence of knowledge on behavior for preventing diabetic foot wounds (p-value 0.001). Meanwhile, the correlation between family support, peer support, and support from health workers in relation to diabetic foot wound prevention behavior was significant, with each showing a p-value of 0.01. Enhancing social support is identified as an effective strategy for reducing the risk of diabetic foot wounds and their associated complications. Therefore, efforts to increase social support levels for diabetes patients should be considered an integral part of their care regimen.